مساهمة علماء القارة الهندية في شرح صحيح مسلم: تكملة فتح الملهم أنموذجا The contribution of scholars of Indian subcontinent in commentary on Sahih Muslim, an introduction to Takmilah Fath al-Mulhim - Mohd Marzuki, Zunaidah (Ulum Hadith Research Centre, USIM, 2019)
Erudite scholars, previously and contemporarily, from different part of the world, have given special attention on Sahih Muslim due to its highest status after Sahih Al-Bukhari. Hence, this study examines the contribution of hadith scholars from the Indian subcontinent in explaining Sahih Muslim, exemplified especially by the book of Takmilah Fath al-Mulhim. The study uses the descriptive analytical approach to portray the types of Sahih Muslim commentaries in general; to mention the contribution of Indian subcontinent scholars; and to briefly explain the description of Takmilah Fath al-Mulhim. This study found that the writing of elucidation, commentary and annotations of Sahih Muslim are available in different languages such as Arabic, Urdu and Persian. Though Takmilah Fath al-Mulhim is written in Arabic like "Fath al-Mulhim", but its style of writing outshines the later. The study also found that Takmilah Fath al-Mulhim used not only Arabic sources but also English, Urdu and Persian which made this book distinguished from all other commentaries of Sahih Muslim.